Prototype development of tethered underwater robot for underwater vessel anchor release - Chukwunazo Joseph, Ezeofor; Oyengiye Moses, Georgewill (Institute of Advanced Engineering and Science, 2020)
Tethered underwater robot (TUR) for underwater vessel anchor release is presented. In off-shore oil and gas enviromnment, there has been series of reported cases on stuck vessel anchors after mooring operations and divers are sent to release these anchors for the vessels to be in motion. The use of divers to perform such function is very risky because of human limitation and some divers have been reported dead on the process due to high pressure underwater or being attacked by underwater wide animals. This has caused very serious panic to the vessel owners and hence, this work is aimed to develop TUR that would be used by the vessel operators instead of divers to release the stuck anchor without loss. The underwater robot system comprises of three basic sections namely graphical user control interface (GUCI) that would be installed in the operator’s laptop, the WiFi LAN router for network connection, and TUR system hardware and software. Each of these sections was strictly designed. Various high-level programming languages were employed to design the GUCI and code the interface buttons, robot controller program codes etc. The implementation carried out and the prototype system tested in the University of Port Harcourt’s swimming pool of 6m depth for validation. The robot performed extremely good in swimming and release of constructed anchor underwater.